Pengaruh Model Pembelajaran Inkuiri Terbimbing Berbantuan Lembar Kerja Mahasiswa terhadap Kesadaran Metakognitif Mahasiswa pada Mata Kuliah Biokimia STKIP-PI Makassar - Gustina, Gustina; Hamsyah, Eka Fitriana; Ahmad, Fandi (Jurnal Kreatif Online, 2020)
This research was an experimental research which aimed to examize the effect of the Student Worksheet (LKM) to inquiry learning model on the metacognitive awareness of students in the STKIP-PI Biochemistry course. The research design was a one group pretest-posttest design. The instrument was a metacognitive questionnaire. The steps of the guided inquiry model consist of orientation, presenting the problem, formulating hypotheses, collecting data, testing hypotheses, and drawing conclusions. Measuring metacognitive awareness refers to the metacognitive categorization guidelines. First, the prerequisite test statistical data was the normality test and the homogeneity test. Hypothesis statistical testing used the help of the SPSS for Windows 17 application through the Paired Sample ttest. The results of inferential statistical analysis using the paired sample ttest obtained a significance result of p = 0.06 > Î± = 0.050, so this states that H0 was accepted and H1 was rejected, which means that there was no effect of guided inquiry learning assisted by LKM on metacognitive awareness of STKIP-PI students.